Sertifikasi dan Upaya Meningkatkan Profesionalitas Guru di MI Misriu Al Hasan Kecamatan Mojo Kabupaten Kediri - Ammar Kukuh Wicaksono; Syafik Ubaidila (Institut Agama Islam Tribakti Kediri, 2020)
Professional teachers are teachers who are competent in their fields. With certification, teacher competence will be further improved in order to better quality education. To be able to take part in the certification program, of course there are several conditions that must be fulfilled by certification participants. Fulfilling the requirements will make it easier to get an educator certificate. After obtaining a certificate, teacher educators must continue to strive to improve performance and professionalism as a form of responsibility as a professional teacher. This research is a qualitative research. Words and actions obtained from interviews are the main data sources in this study, while additional data is in the form of documents. The results of this study are, 1. The terms and patterns that are passed by the teachers at MI Misriu Al Hasan are in accordance with the applicable regulations, there are three patterns that are followed, namely Portfolio, PLPG and PPG, 2. Efforts that have been made by certification teachers in MI Misriu Al Hasan Kraton Mojo Kediri in improving professionalism, including by increasing discipline, using appropriate and effective teaching methods, preparing themselves and materials that have been planned before carrying out learning, providing problem solving to students with problems intensively and participating in activities of professional organizations such as PGIN and KKG and NU community organizations. Other supporting activities include training and seminars. [Guru yang professional adalah guru yang berkompeten dibidangnya. Dengan sertifikasi, kompetensi guru akan lebih ditingkatkan lagi guna kualitas Pendidikan yang lebih baik. Untuk dapat mengikuti program sertifikasi tentu ada beberapa ketentuan yang harus dipenuhi oleh para peserta sertifikasi. Pemenuhan persyaratan akan mempermudah dalam mendapatkan sertifikat pendidik. Setelah mendapat sertifikat pendidik guru harus terus berupaya meingkatkan kinerja dan profesionalitas sebagai bentuk tanggung jawab sebagai seorang guru professional. Penelitian ini merupakan penelitian kualitatif. Kata-kata dan tindakan yang diperoleh dari wawancara merupakan sumber data utama dalam penelitian ini, sedangkan data tambahan berupa dokumen-dokumen. Hasil penelitian ini yaitu, 1. Syarat dan pola yang dilalui oleh guru-guru di MI Misriu Al Hasan telah sesuai dengan ketentuan yang berlaku, ada tiga pola yang diikuti yaitu Portofolio, PLPG dan PPG, 2. Upaya yang telah dilakukan oleh guru sertifikasi di MI Misriu Al Hasan Kraton Mojo Kediri dalam meningkatkan profesionalitas diantaranya dengan meningkatkan kedisiplinan, mengunakan metode mengajar yang sesuai dan efektif, mempersiapkan diri dan materi yang telah direncanakan sebelum melaksanakan pembelajaran, memberikan problem solving pada siswa bermasalah dengan intensif serta mengikuti kegiatan organisasi profesi seperti PGIN dan KKG serta organisasi kemasyarakatan NU. Kegiatan penunjang lain berupa diklat dan seminar]